Low-cost analytical tools for compositional analysis of particulate matter - Mettakoonpitak, Jaruwan, author; Henry, Charles, advisor; Farmer, Delphine, committee member; Barisas, George, committee member; Volckens, John, committee member (Colorado State University. Libraries, 2018)
Particulate matter (PM) represents a major health problem to people worldwide, contributing to 4 million deaths annually as reported by the Global Burden of Disease (GBD) study (http://www.healthdata.org). PM toxicity is linked to its chemical composition. The toxic chemical components of PM include trace metals, reactive oxygen species, and organic compounds that cause DNA oxidative damage and/or carcinogenesis in the respiratory and cardiovascular systems. The advanced laboratory instrumentation, normally used for the compositional analysis in PM, hinders people in remote area accessing PM monitoring on time due to large, complicated, and expensive features. Microfluidic paper-based analytical devices (mPADs) allow people in developing countries and remote area get an access to analytical testing in wide-ranging application from pharmaceutical analysis to environmental monitoring. However, analytical performance of mPADs needs to be improved. Electrochemistry, integrated into an mPAD, is able to improve limits of detection (LOD) and selectivity. This dissertation presents two efforts towards developing low-cost, portable, and disposable electrochemical analytical devices for chemical characterization of PM. First, simple electrochemical devices for analyzing trace metals including Zn, Cd, Pb, Co, and Ni in PM are presented. The device was fabricated using stencil-printing on a low-cost polyethylene transparency (PET) sheet to create carbon stencil-printed electrode (CSPE). For simultaneous Zn, Cd, and Pb detection, electrospray deposition of silver nanoparticles (AgNPs) was chosen for electrode modification to enhance electrode performance. An enhanced dispersion of AgNPs on the electrode surface was observed resulting in increase of surface area and better electrochemical performance. In addition, Bi and Nafion were used as co-modifiers to enhance peak current. Finally, acetate buffer (pH 5.0) was found to be suitable to obtain the best limit of detection (LOD) and longest linear operating range. The AgNP/Bi/Nafion-modified CSPE provided LODs of 5.0, 0.5, and 0.1 μg L-1 for Zn, Cd, and Pb detection, respectively. The proposed method was used to measure Zn, Cd, and Pb in PM samples including incense, fly ash, cigarette, and solder. The results from the proposed method for Zn, Cd, and Pb detections were not significantly different from the results measured using ICP-MS (at 95% confidence). Besides the method developed for Zn, Cd, and Pb detection, CSPEs were also used for Co and Ni analysis because these metals can produce reactive oxygen species via Fenton-like reactions. The CSPE for Co and Ni determination was modified with Bi to improve signal. Furthermore, dimethylglyoxime (DMG) was used as a Co(II) and Ni(II) chelator with highly selective chemical precipitation for adsorptive stripping voltammetry. The approach gave LOD of 1.0 and 5.0 μg L-1 for Co and Ni, respectively. Finally, Bi-modified CSPEs were used to determine Co and Ni in aerosol samples. The amount of Co and Ni in the samples determined using the proposed method was not significantly different from the results obtained using ICP-MS at 95% confidence. In addition to metals, other components in PM such as organic compounds are prevalent in PM but their analysis is normally restricted to complicated separation methods. To address this need, the last part of this dissertation focuses on developing a low-cost, high resolution electrophoretic laminated Parafilm-paper devices for further analysis of complicated compositions in PM samples. The essential electrophoretic parameters including Joule heating, electroosmotic flow, and electrophoretic mobility were studied. Colorimetry and fluorescence were used as the detection methods. Method viability was first established using chlorophenol red and indigo carmine dyes. The parameters affecting the separation included paper type, channel width, and applied potential. Addition of an injection valve into the device improved resolution and reduced peak broadening. Moreover, the separation of fluorescein isothiocyanate (FITC) and glutamic acid labeled with FITC was used to demonstrate fluorescence detection. In conclusion, the low-cost methods for PM analysis were proposed with using CSPE to detect Zn, Cd, Pb, Ni and Co and using electrophoresis separation on mPAD prepared for effective complicated compounds analysis in the future.
Keywords: electrophoretic microfluidic paper-based analytical devices; particulate matter analysis; metal detection; electrochemical paper-based analytical devices